2014
DOI: 10.1108/gm-02-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Women tourism entrepreneurs: doing gender on farms in Sweden

Abstract: Purpose – This paper aims to explore how gender is “done” on farms in Sweden in the context of increased tourism and hospitality activities. The authors seek to investigate how gender is done vis-à-vis women’s farm tourism entrepreneurship. They seek to answer the questions: What has motivated the farm women to become tourism entrepreneurs? How are the gendered divisions of labor changed through women starting businesses? How does the gendered associated symbolism, as well as the identities, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 48 publications
0
25
0
6
Order By: Relevance
“…Pettersson and Heldt, 2014), research on sustainable entrepreneurs lacks a gender perspective. We have found that research in sustainable business start-ups has to date widely neglected gender as a factor or dimension in the analysis.…”
Section: Gender and Motivationmentioning
confidence: 99%
“…Pettersson and Heldt, 2014), research on sustainable entrepreneurs lacks a gender perspective. We have found that research in sustainable business start-ups has to date widely neglected gender as a factor or dimension in the analysis.…”
Section: Gender and Motivationmentioning
confidence: 99%
“…As an illustration, Lewis accounts for how women entrepreneurs make entrepreneurial practice gender-neutral (Lewis, 2006), or negotiate between an expressive femininity and a professional masculinity (Lewis, 2013). Pettersson and Cassel (2014) analyse how women entrepreneurs construct their identities by moving between a position of family and domestic tasks and one of public and instrumental business responsibilities.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, this line of research (e.g. Díaz-García and Welter, 2010;Pettersson and Cassel, 2014;Maden, 2015;Lewis, 2013) has not explored the distinctions of women's identities according to their business backgrounds, and how women with identical backgrounds collectively construct their entrepreneurial identities, when they have the opportunity to interact with each other and share their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…of the society that determine the collective and individual perception of entrepreneurial women, stereotypes, gender roles,Gupta (2014),Luke and Munshi (2010),Clark (2013),Lindberg et al (2014),Gicheva and Link (2015),Noguera et al (2013),Urbano and Turró (2013), Ezzedeen and Zikie (2012),Pettersson and Heldt (2014) F12Culture,Shinnar (2012), Hechevarría(2015), Marcén (2014), Overbeke et al (2013), Aramand (2012) F13 Politics and government Government politics for entrepreneurship support, Sullivan and Meek (2012), Cho and Honoreti (2014), Ahl (2015), Pettersson (2012), Lockyer and George (2012), Lakovleva et al (2013), Ming Yen Teoh and Choy Chong (2014) Public expense in services for children care, Elam and Terjesen (2010), Ming Yen Teoh and Choy Chong (2014) Legal frame and government politics, Estrin and Mickiewicz (2011), Luke and Munshi (2010), Clark (2013), Hansson (2010), Rostam-Afschar (2013) National system of investigation and innovation, Dawson and Henley (2012) Size of the state sector, Bardasi et al (2011), Estrin and Mickiewicz (2011)Ϫ F14 Macro-economic situation, Minnitti and Naudé (2010), Zhang et al (2012), Floro et al (2013), Klyver et al (2013), Saridakis et al (2014) F15 Rule of law (violence against women and mobility restrictions of women), Estrin and Mickiewicz (2011) F16 Women situation presence of woman in business leadership positions, Elam and Terjesen (2010), Clark (2013), Kobeissi (2010) Female work rate in industrial, agricultural and services, Elam and Terjesen (2010) Salary gap between men and women, Elam and Terjesen (2010), Kobeissi (2010) Meso environment F17 Conditions for businesses (legal frame, infrastructure, services, in between others), Hampel-Milagrosa (2010), Minniti and Naudé (2010), Urbano and Turró (2013), Welter and Smallbone (2010), Dahlstrand and Politis (2013) F18 Attitude towards women inside the formal financing system, Minniti and Naudé (2010), Rogers (2012), Bellucci et al (2010) F19 Lack of alternative and unemployment, Dawson and Henley (2012) Micro environment F20 Personal networks Family ties and close contacts, network of social contacts, Minniti and Naudé (2010), Sullivan and Meek (2012), Moutinho et al (2014), Poon et al (2012), Zhang et al (2012) Antecedents and family support, Sullivan and Meek (2012), Hoffmann et al (2014), Verheul et al (2012) (a) F21 Professional and entrepreneurial networks, Sullivan and Meek (2012), Brogen et al (2013) F22 Family demands Minniti and Naudé (2010), Overbeke et al (2013), Agarwal (2015), Lewis et al (2015) F23 Resources Availability, Dawson and Henley (2012), Lindholm and Politis (2013), Rogers (2012) Capital restrictions and initial costs, Minniti and Naudé (2010), Radhakrishnan (2015), Kariv and Coleman (2015), Lakovleva et al (2013) Cost of resources, Wu (2012) F24…”
mentioning
confidence: 99%